Factibilidad de lechuga lactuca sativa hidropónica en el cantón Santa Rosa provincia de El Oro - Castillo Bejarano, Jhonson Fabricio (2018)
Hydroponic crops are an effective alternative to solve the lack of food worldwide, by sectors of the population with a deficit of monetary income for the acquisition of product. These systems of crops without soil have expanded to global levels, in areas that are not habitable for the production of crops, taking advantage of unconventional areas for planting them, implementing sustainable urban farms, hand in hand with urban agriculture, this has increased positive way in hydroponic systems the control and more efficient management of resources. With the increase of the population, the lack of soil for agricultural use and the high levels of contamination; the hydroponic technique, provides an alternative of effective production, with respect to the traditional crop. At present, the implementations of prohibited pesticides, with high toxins, in agricultural productions; Hydroponics ensures an effective control management with respect to plant health regulations. Which, has induced a massive application of production with the hydroponic system in crops such as vegetables, fruits, forage for animals. The present work shows, the feasibility of the NFT hydroponic system, through an economic evaluation. Two specific objectives were proposed, of which the first was to design the model of lettuce production using the NTF system of hydroponics, and the other objective of the present research is to establish the economic profitability that the production of hydroponic lettuce would generate through research methods and financial studies. Therefore, the general objective of the present investigation was to determine the economic feasibility of the hydroponic system for the production of lettuce, through the recirculation of water, recycling materials and the use of free spaces. Obtained the results of the research carried out on the feasibility of lettuce (Lactuca Sativa) hydroponic in the canton Santa Rosa, El Oro Province, we reached the following conclusions: The hydroponic production system can be developed as part of family farming due to the relative ease with which this system can be implemented, with the aim of covering food for each of the households and also as a possible source of income. According to the economic evaluation, the indicators are favorable to be able to develop the project, which is why we obtain a Net Actuation Value (NPV), an Internal Rate of Return (IRR) and a positive Benefit / Cost Ratio and that leads us to conclude that the project is profitable from the economic point of view. In the productive issue we came to the conclusion that the combination of technology and planting of crops is feasible, with this it was possible to take advantage in a more efficient way the production of the crop in a reduced space. When executing the project it is allowed to obtain the following experiences: prevent direct entry, in the NFT hydroponic system, of the sunlight, providing a roof where heat can be taken care of in the crop. It is advisable to buy fully germinated plants for direct transplant in the system, this achieves greater efficiency in production and faster harvest. By them we refer to the nutritive solutions used in this project. It is recommended that in order to obtain greater returns or benefits, the project space could be expanded, with this one could think or obtain an ecological certification for greater confidence by consumers in the quality of the product.